Site assessment and remediation for environmental engineers - Surbeck, Cristiane Q.; Kuo, Jeff (Boca Raton, FL : CRC Press, 2021)
'This book serves as a primary textbook for environmental site investigation and remediation of subsurface soil and groundwater. It introduces concepts and principles of field investigative techniques to adequately determine the extent of contamination in the subsurface for the selection of clean-up alternatives. It then focuses on practical calculations and skills needed to design and operate remediation systems that will both educate students and be useful for entry-level professionals in the field. Examines the practical aspects of investigating and cleaning up contaminated soil and groundwater. Contains scenarios, illustrations, equations, and example problems with discussions that illustrate various practical situations and interpret the results. Includes end-of-chapter problems to reinforce student learning. Provides a regulatory context, risk-based remediation goals, as well as public and community involvement scenarios. Discusses sustainability and performance assessment of the remediation methods presented. Site Assessment and Remediation for Environmental Engineers provides upper-level undergraduate and graduate students with practical, project-oriented knowledge of how to investigate and clean up a site contaminated with chemicals and hazardous waste'--
Includes bibliographical references and index.
Keywords: Hazardous wastes -- Risk assessment; Hazardous waste site remediation; Hazardous waste sites -- Evaluation